2005
DOI: 10.1007/s00192-005-1346-x
|View full text |Cite
|
Sign up to set email alerts
|

Laparoscopic uterosacral ligament uterine suspension compared with vaginal hysterectomy with vaginal vault suspension for uterovaginal prolapse

Abstract: This study compares the outcomes of laparoscopic uterosacral ligament uterine suspension (LUSUS) to those of vaginal vault suspension with total vaginal hysterectomy (TVH) for the treatment of symptomatic uterovaginal prolapse. We compared the outcomes of 25 LUSUS to those of 25 TVH with vaginal vault suspension among age-matched controls. No significant complications occurred in either group. EBL and hospitalization duration were significantly less in LUSUS patients (72 cc vs. 227 cc, P < .0001 and 1.05 vs. 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
56
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 88 publications
(60 citation statements)
references
References 10 publications
0
56
0
Order By: Relevance
“…Therefore, 15 studies were excluded. Twenty-three studies were available in which outcome data for 1,764 women who underwent a vaginal hysterectomy for prolapse symptoms were analyzed separately, with a follow-up of between 9 and 60 months [4,5,6,[9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28].…”
Section: Study Selectionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, 15 studies were excluded. Twenty-three studies were available in which outcome data for 1,764 women who underwent a vaginal hysterectomy for prolapse symptoms were analyzed separately, with a follow-up of between 9 and 60 months [4,5,6,[9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28].…”
Section: Study Selectionmentioning
confidence: 99%
“…In a review of the literature, it was concluded that a vaginal hysterectomy is unlikely to cause bladder and bowel dysfunction [60]. The occurrence of de novo stress incontinence after a vaginal hysterectomy for uterine descent was reported in between 0% and 22% of women [6,14,17,23,24].…”
Section: Anatomical Curementioning
confidence: 99%
“…Several alternative operations for prolapse repair with uterine preservation, using either a vaginal or an abdominal approach, have been proposed (1,2,(12)(13)(14)(15)(16)(17)(18)(19)(20).…”
Section: Discussionmentioning
confidence: 99%
“…Laparoscopic ventrosuspension involves suturing of the round ligament to the rectal sheath; however, this is associated with a poor success rate, with one case series of nine women reporting recurrence of prolapse in eight women within 3 months of surgery. 14 Laparoscopic uterosacral plication, first described in 1997, involves placing three purse-string sutures from the uterosacral ligaments to the posterior cervix: 15 Wu 16 reported a case series of seven women with no recurrence of prolapse at 9-17 months follow-up. Laparoscopic suture hysteropexy with closure of the pouch of Douglas and plication and reattachment of the uterosacral ligaments to the cervix has been reported by Maher et al, 17 with an objective success rate of 79% in 43 women after a mean follow-up of 12 months.…”
Section: Discussionmentioning
confidence: 99%